Milk Production of Holstein Friesian Dairy Cows in Various Lactation Periods (Case Study at Capita Farm, Semarang, Central Java) - Rudy Hartanto; Alvian Adhi Pamungkas; Edi Prayitno; Dian Wahyu Harjanti (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2020)
The purpose of this research was to determine and to assess the milk production of Holstein Friesian cows in Capita Farm based on its lactation period. The research was conducted on 29thSeptember – 28thOctober 2019. The materials used in the study were 59 FH dairy cows in the lactation period of 1-6 and lactation months of 1-10. The body weight was 497.71 ± 44.73 kg and the milk production was 14.43 ± 4.43 liters / day / head. The study was conducted by observation. The parameters observed were the lactation period and daily milk production. Afterward, the daily milk production was converted into milk production in one lactation period. The difference in milk production of one lactation period between the lactation periods was determined by the independent sample t test at level of 5%. The results of this research showed that the peak production in the 4th lactation period was 4458.26 liter/lactation, while the 1st, 2nd, 3th, 5th, 6th lactation periods were 3976.85; 4100.01; 4143.85; 3850.27; 2938.56 liter/lactation, respectively. The 6th lactation period was significantly lower than the others withproduction capability of 65.91% of the mature equivalent (ME). It was concluded that the Holstein Friesian dairy cows inCapita Farm has the highest production in the 4th lactation period, but there is a real difference in production when it enters the 6thperiod.